The Development of Agreement Types of Neuter Nouns in Slovenian - Sušnik, Miha (Jezikoslovni zapiski, 2024)
This article first lays out an explicit theoretical approach to grammatical gender, separately examining both the synchronic and diachronic perspectives. It then describes so-called agreement types of (original) neuters (i.e., types of noun phrases containing agreeing words with regard to their morphological and morphosyntactic properties), which serve as representations of the main paths of development of the neuter gender in Slovenian. Although the works of Oblak (1888, 1890), Tesnière (1925b), and Ramovš (1935, 1952) have already provided several solutions, many issues regarding the development of the neuter gender in Slovenian still remain unresolved.